PERANCANGAN APLIKASI PENGADUAN MASYARAKAT DESA BEBER BERBASIS ANDROID - Putra, Lalu Herjayadi; Hamdi, Saeful; Zulkarnaen, Muhammad Fauzi; Fadli, Sofiansyah (Teknik: Jurnal Ilmu Teknik dan Informatika, 2022)
Until now, the Beber Village Government, community complaints still have to go to the village office, Kadus houses or BPD. Complaints like that, of course, will take a little time and take a little longer. Data on public complaints is not stored as evaluation Material for evaluation and preparation of the RKPDes. Information submitted from the village government took a long time to reach the community. Although basically now there is a name WhatsApp, the public can also send WhatsApp messages by sending evidence of events and others. However, the complaint message will not be stored in its entirety, even a few days after the message arrives, it's easy to be crushed by other messages, making it difficult to find it again. In connection with the problems above, the researchers tried to design an application entitled Beber Village Community Complaints. In designing this application, the author uses the SDLC Waterfall model method, which is carried out step by step in accordance with the procedures in the Waterfall method. The admin application is built using the Codeigniter Framework version 3 with the PHP programming language. While the client/user uses Android which is built with the Flutter Framework which uses the Dart programming language. The resulting application is in the form of a Client Server. Adam uses the WEB Service view while the client/user uses the Android version. This application will exchange information between the community and the village and between the village and the community. This application aims to make it easier for both the community and the village in exchanging information, which then the information data can be stored intact in the database